2017
DOI: 10.5688/ajpe816100
|View full text |Cite
|
Sign up to set email alerts
|

Transition and Student Well-being – Why We Need to Start the Conversation

Abstract: Every year our pharmacy programs enroll new students. Some of these students will transition smoothly, but others may not transition optimally. This transition issue can have potentially severe mental health consequences and be caused by a multitude of factors. We need to identify these factors, be able to identify at-risk students, and have programs in place to help better support our students' mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Our study highlights a need for students to be prepared for high levels of cognitive load. 11 This could be supported through reflection, such that students know themselves better, are aware of their thoughts, and can predict reactions to experiences that may be unsettling and potentially negative. Integrating reflective practice with knowledge and skill development may also prevent "ironic rebound," and so the full extent of learning may be realized more readily.…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlights a need for students to be prepared for high levels of cognitive load. 11 This could be supported through reflection, such that students know themselves better, are aware of their thoughts, and can predict reactions to experiences that may be unsettling and potentially negative. Integrating reflective practice with knowledge and skill development may also prevent "ironic rebound," and so the full extent of learning may be realized more readily.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, both anecdotal and empirical evidence suggest that health professions students struggle with fatigue and burnout in one or more domains that could be considered counter to wellbeing. [25][26][27][28] Stoffel and Cain's recent review of the grit and resilience literature in the health professions reveals the dearth of information specific to pharmacy education. 29 Overall, as compared to physicians and nurses, we know relatively little about wellbeing within the pharmacy profession.…”
Section: The Case For Fostering Wellness and Wellbeingmentioning
confidence: 99%
“…[5][6][7] While this is somewhat common knowledge and many students adopt these behaviors as a stress coping mechanism, there are still significant numbers of students who do not. [8][9][10][11] Several studies have shown that college students have difficulty in establishing and maintaining health-promoting behaviors. 12 Although many colleges and schools may offer formal and informal information sessions encouraging students to take proactive measures toward improving their health and wellbeing, research literature regarding the effectiveness of these sessions in influencing students' well-being behaviors is sparse.…”
Section: Introductionmentioning
confidence: 99%